2019
DOI: 10.1038/s41388-019-1085-y
|View full text |Cite
|
Sign up to set email alerts
|

DEPTOR is an in vivo tumor suppressor that inhibits prostate tumorigenesis via the inactivation of mTORC1/2 signals

Abstract: The DEPTOR-mTORC1/2 axis has been shown to play an important, but a context dependent role in the regulation of proliferation and the survival of various cancer cells in cell culture settings. The in vivo role of DEPTOR in tumorigenesis remains elusive. Here we showed that the levels of both DEPTOR protein and mRNA were substantially decreased in human prostate cancer tissues, which positively correlated with disease progression. DEPTOR depletion accelerated proliferation and survival, migration, and invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Our results indicated that FDFT1 expression is negatively correlated with mTOR expression. Consistent with the data in previous reports 27,[57][58][59][60] , our data showed that mTOR is a positive regulator of aerobic glycolysis and proliferation in CRC cells. HIF1α is a key regulator of the Warburg effect and regulates the expression of a variety of metabolism-related proteins 61 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that FDFT1 expression is negatively correlated with mTOR expression. Consistent with the data in previous reports 27,[57][58][59][60] , our data showed that mTOR is a positive regulator of aerobic glycolysis and proliferation in CRC cells. HIF1α is a key regulator of the Warburg effect and regulates the expression of a variety of metabolism-related proteins 61 .…”
Section: Discussionsupporting
confidence: 93%
“…Among genes that were co‐bound by HNF1A/KDM6A and downregulated in Kdm6a pKO and Hnf1a aKO pancreas, we identified several negative regulators of EMT such as Foxa3 (Jagle et al , ) and Deptor (Chen et al , ) as well as negative MAPK regulators such as Gstp1 (Ruscoe et al , ; Xue et al , ) and Ptprj (Sacco et al , ) (Fig EV3T and U). These findings, therefore, indicated that the derangement of shared biological pathways in Kdm6a pKO and Hnf1a aKO mice (shown in Fig EV3L) was largely due to the deregulation of common direct target genes.…”
Section: Resultsmentioning
confidence: 96%
“…This result is consistent with previous ndings. [31,32]. In addition, SOX2 as a stem-like transcription factor could promote EMT [32,33].…”
Section: Discussionmentioning
confidence: 99%